Postgraduate studies qualifying for teaching mathematics as another subject - Barańska, Barbara; Zambrowska, Małgorzata (Annales Universitatis Paedagogicae Cracoviensis | Studia ad Didacticam Mathematicae Pertinentia, 2024)
The idea for the project was inspired by experiences and observations related to postgraduate studies qualifying for teaching mathematics as a second subject (PSQTM). One important goal of the project was a comprehensive analysis of the issues related to postgraduate mathematics teacher education. In the project we wanted to diagnose substantive and didactic competences of teachers taking postgraduate studies qualifying for teaching mathematics as another subject in primary and secondary school.